Determinan Perilaku Pengelolaan Keuangan di Kecamatan Kajoran Kabupaten Magelang - Agung Nurrohmat; Himawan Arif Sutanto (Sekolah Tinggi Ilmu Ekonomi Bank BPD Jateng, 2021)
Financial management behavior is one of the main topics of discussion at this time. Because it is related to consumptive behavior in the community in Indonesia, and especially in the community of Kajoran sub-district. This research aims to determine the effect on financial literacy, financial attitude, income and locus of control financial management behavior. 100 people take as respondent using accidental sampling method. Analytical method uses linear regression test. The research show that financial literacy, financial attitude and locus of control have positive effect on financial management behavior. While income doesn’t affect on financial management behavior